Metsovo Lung: History of Population Environmental Exposure - C. Sxiza; N. Zagorianakou; C. Vlami; G. Farantos; V. Rapisarda; G. Dounias (European Scientific Journal, ESJ, 2024)
The historical course of the Metsovo Lung phenomenon began to be investigated in the 1980s when extensive pleural calcifications causing malignant mesothelioma appeared at a high frequency beyond expectation. It was not possible to explain their frequency. This finding reasonably raised the question of whether it was indeed tuberculous pleurisy or something else. The biopsies carried out confirmed that these were tremolite asbestos fibres. These fibres were derived from a shielding material containing asbestos. This is a global phenomenon according to which the entire population of Metsovo was exposed to asbestos, without knowing it, from a traditional shielding material. The abandonment of the material and its non-use brought about a gradual reduction of the phenomenon, which also marks the reduction of mesothelioma.